Analisis Pengukuran Taraf Intensitas Bunyi Pengeras Suara Masjid Menggunakan Aplikasi Sound Level Meter - Nurizati, Nurizati; Sumardi, Tedi; Robiyana, Iqbal (Jurnal Riset Fisika Indonesia, 2024)
Noise pollution can come from various sources around us, such as loudspeakers. In Indonesia, where the majority of the population is Muslim, many mosques use loudspeakers to broadcast the adhan, or call to prayer. Recently, the use of mosque loudspeakers has sparked debate, as some people are concerned that the noise may disrupt their comfort and potentially affect their health. This study aims to assess whether the noise level of the adhan from these loudspeakers is within safe limits or exceeds the threshold that could harm human health. The research involved measuring the sound intensity of the adhan using a sound level meter app. Measurements were taken at two locations: within the mosque courtyard and at a distance of 100 meters from the mosque. The study examined six mosques in Bekasi City, with two mosques located in residential areas, two in office areas, and two in school areas. The results indicate that the highest noise levels were recorded in the mosque courtyards, with levels decreasing as the distance from the mosque increased. Among the six mosques, the highest noise level recorded was 84.5 dB in the mosque courtyard, which is below the threshold set by the Ministry of Manpower Regulation No. 5 of 2018, meaning it is still considered safe for human health